Challenges and Opportunities for Special-Needs Children in Elementary Schools - Fajri, Bayu Ramadhani; Jauhari, Muhammad Nurrohman (LPPM Universitas Pelita Bangsa, 2024)
This research explores the challenges and opportunities for inclusive education for special-needs children in elementary schools in Indonesia. It examines the impact of government policies, the actual conditions in the field, and the availability of supporting facilities and resources. The study utilizes a qualitative method with a case study approach, involving various stakeholders such as special-needs children, teachers, parents, and school principals as informants. Findings indicate that while government policies have improved access to education for special-needs children, there are disparities in implementation and resource allocation among schools. Teachers face obstacles due to a lack of specialized training and high workloads, while limited facilities and stigma also hinder inclusive education. The research emphasizes the need for continuous support, changes in community attitudes, and improvements in teacher training and facilities to ensure effective inclusive education for special-needs children in elementary schools.